PENGARUH LEVERAGE DAN STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA - Anggita Noviandini; Emma Saur Nauli S (EBID: Ekonomi Bisnis Digital, 2023)
This study aims to determine what factors influence Earnings Management by explaining empirical evidence regarding the effect of Leverage, Managerial Ownership, Institutional Ownership, and Firm Size as control variables. This study uses secondary data. The independent variables in this study are Leverage, Managerial Ownership and Institutional Ownership. The dependent variable in this study is Earnings Management. The control variable in this study is company size. The research data was obtained from annual reports published on the Indonesia Stock Exchange for 2019 – 2021. The sampling technique used was purposive sampling which obtained a total of 72 companies in mining companies listed on the Indonesia Stock Exchange in 2016 and homogeneous. This study uses multiple regression analysis method. The results of this study are (1) Leverage Has a Positive and Significant Effect on Earnings Management; (2) GCG KI does not have a positive effect on earnings management; (3) GCG KM does not have a positive effect on profit management; (4) Company Size Has a Positive and Significant Influence on Earnings Management.